Glycosylated and non-glycosylated quantum dot-displayed peptides trafficked indiscriminately inside lung cancer cells but discriminately sorted in normal lung cells: An indispensable part in nanoparticle-based intracellular drug delivery - Roger Salvacion Tan (Elsevier, 2018)
Difference in sub-cellular trafficking of glycosylated and naked peptides, between normal and lung cancer cells, was established. Normal lung tissue discriminately sorted glycosylated from non-glycosylated peptides by allowing golgi localization of the glycosylated peptides while restricting golgi entry of the naked peptides. This mechanism was surprisingly not observed in its cancer cell counterpart. Lung cancer cells tend to allow unrestricted localization of both glycosylated and naked peptides in the golgi apparatus. This newly discovered difference in sub-cellular trafficking between normal and lung cancer cells could potentially be used as an effective strategy in targeted intracellular delivery, especially targeting golgi-resident enzymes for possible treatment of diseases associated with glycans and glycoproteins, such as, congenital disease of glycosylation (CDG). This very important detail in intracellular trafficking inside normal and cancer cells is an indispensable part in nanoparticle-based intracellular drug delivery. Keywords: Intracellular trafficking, Peptides and glycopeptides, Lung cancer cells, Normal lung tissue, Golgi localization, Quantum dots